Natural resource and environmental economics - Perman, Roger, 1949-; UGent. Faculteit Bio-ingenieurswetenschappen. Vakgroep Landbouweconomie; Ma, Yue, 1963-; McGilvray, Michael, ....- (Harlow : Pearson education, 2003)
This text has been written primarily for the specialist market of second and third year undergraduate and post-graduate students of economics. The clear explanations and basic principles that underpin the text, however, make it readily accessible to non-economists coming to environmental economics from diverse programmes of study. Natural Resource and Environmental Economics is among the leading textbooks in its field. Well written and rigorous in its approach, this third edition follows in the vein of previous editions and continues to provide a comprehensive and clear account of the application of economic analysis to environmental issues. This new edition has evolved with the times and been thoroughly updated to reflect recent developments in environmental issues and policies, such as forestry, biodiversity and pollution control. The early chapters explain the development and role of environmental economics before further chapters advance the student at a suitably challenging but achievable level.
Handboek bij cursus "Economics and Management of Natural Resources" (Guido Van Huylenbroeck) (Stijn Speelman)
Keywords: Environmental economics; Natural resources -- Management; Social Sciences and Humanities. Economics -- Environmental Economics; Sustainable development